1991
DOI: 10.1007/bf00266772
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of cathepsins B, H, and L in the rat gastro-duodenal mucosa

Abstract: Cathepsins B, H, and L are representative cysteine proteinases in lysosomes of a large variety of cells. Previous immunochemical studies indicated the presence of these enzymes also in the gastrointestinal wall. Using specific antisera, the cellular and subcellular distribution of cathepsins B, H, and L in rat gastric (oxyntic and pyloric part) and duodenal mucosa was investigated by light and electron microscopical immunocytochemistry. The subtypes of cathepsins were distributed differently in the cellular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The expression of cysteine proteases (cathepsins B, L, and H) has been described in the mucosa of the gastrointestinal tract, and these enzymes were histochemically localized to enterocytes of the rat duodenum (33). We performed an analysis of both the cysteine and aspartyl-protease activity in our human IEC lines.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of cysteine proteases (cathepsins B, L, and H) has been described in the mucosa of the gastrointestinal tract, and these enzymes were histochemically localized to enterocytes of the rat duodenum (33). We performed an analysis of both the cysteine and aspartyl-protease activity in our human IEC lines.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that cathepsin L is localized in Kupffer cells of the liver and macrophages in the lung and intestine (Ii et al 1985;Watanabe et al 1989;Furuhashi et al 1991;Ishii et al 1991). The present results, using ISH, confirmed that cathepsin L mRNA was specifically detected in Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, cathepsins B and H are localized in lysosomes of both hepatocytes and Kupffer cells, while cathepsin L is more intensely detected in Kupffer cells than in hepatocytes (27). Interestingly, duodenal epithelial cells contain lysosomes immunopositive for cathepsins B and L, but not for cathepsin H, which is intensely localized in lysosomes of macrophages in the lamina propria (24). It is well known that the epididymal ducts are divided into several segments that differ functionally as well as morphologically (6).…”
mentioning
confidence: 98%
“…Takahashi et al (79) have shown that cathepsin B activates prorenin into active renin. In fact, cathepsin B or H has been demonstrated to be localized in secretory granules of some peptidehormone producing cells including those producing active renin (24,28,52,69,92,93,101,102,112), suggesting that cathepsins B and H may participate in the activation processes of bioactive proteins and peptide hormones. Therefore, it is also important to examine the roles of the cysteine proteinases in the extralysosomal compartments of the cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation